2006
DOI: 10.1111/j.1365-2516.2006.01302.x
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing of the factor 8(F8) coding regions in 10 Turkish hemophilia A patients reveals three novel pathological mutations, and one rediagnosis of von Willebrand's disease type 2N

Abstract: The most common cause for severe cases of hemophilia A is the homologous recombination involving intron 22 and related sequences outside the F8 gene. F8 coding regions of the gene including the exon/intron junctions were sequenced in 10 Turkish hemophilia A patients all of whom have been typed negative for intron 22 inversion and who did not have a detectable change by DGGE analysis. Pathological changes including two novel deletions (c. 205del CT and c. 3699del ACAT), one novel missense mutation (9546A) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 9 publications
2
3
0
1
Order By: Relevance
“…Thus, the sensitivity of DHPLC was around 90% (20/23 identified changes), similar to that already reported [4]. Furthermore, it suggests that the rate of misdiagnosis should be low, although sporadic cases of misdiagnosis with type 2N VWD are still reported [15].…”
Section: Discussionsupporting
confidence: 85%
“…Thus, the sensitivity of DHPLC was around 90% (20/23 identified changes), similar to that already reported [4]. Furthermore, it suggests that the rate of misdiagnosis should be low, although sporadic cases of misdiagnosis with type 2N VWD are still reported [15].…”
Section: Discussionsupporting
confidence: 85%
“…We failed to identify any mutation in two male patients (6.5% of examined patients) even after a complete sequencing of the coding regions and splice junctions of the F8 gene (Table 1). This phenomenon seems not uncommon as it was also observed in many other studies [25–27]. In these studies, it was reported that the proportion of patients with undetected F8 mutations varies between 1.5 and 15%.…”
Section: Resultssupporting
confidence: 66%
“…Inhibitor information was available for one high-responder patient with a large deletion and two low-responder patients with a missense mutation and a small deletion [15,21]. With these additional three patients who had severe phenotype and very low levels of FVIII : C, the total number of the high-responder and lowresponder patients were 30 and six, respectively ( Table 4).…”
Section: Identification Of Mutations In Severe Hemophilia a Patients mentioning
confidence: 99%